Standards to Support Development of Terminological Systems for Healthcare Telematics - Rossi Mori, A.; Consorti, F.; Galeazzi, E. (Methods of Information in Medicine, 1998)
The Technical Committee on “Medical Informatics” of the European Committee for Standardization (CEN{TC251) is supporting developers ofterminological systems in healthcare by a series of standards. The dream of “universal” coding system was abandoned in favor of a coherent family of terminologies, diversified according to tasks; two ideas were introduced: (1) the “categorical structure”, i.e. a model of semantic categories and their relations within a subject field and (2) the “cross-thesaurus”, i.e. a system of descriptors to build a systematic representation (called here “dissection") for each terminological phrase, coherent across diverse terminologies on a given subject field.The goal is to assure coexistence and interoperability (and reciprocal support for development and maintenance) to three generations of systems: (1) traditional paper-based systems (first generation); (2) compositional systems built according to a categorical structure and a cross-thesaurus (second generation) and (3) formal models (third generation).Various scenarios are presented, on the exploitation of computer-based terminological systems. The idea of “operational meaning” of terminological phrases within administrative and organizational contexts and the idea of “task-oriented details” are also introduced, to justify and exploit design constraints on terminological systems.
Keywords: Healthcare Standards; Terminology Systems